Uniqueness Of Larval Releasing Of Littoraria Scabra L. (Gastropoda: Littorinidae), In Tombariri Mangrove, North Sulawesi,Indonesia - Lalita, Jans D (Jurnal Ilmiah PLATAX, 2018)
This research was found the novelty of reproduction strategy uniqueness of L. scabra that very rare in nature, reverse male function fertilized eggs are sucked for brooding in the mantle of male up to hatching as veligers, and thus, the males are capable of releasing the larvae in the full and new moon at spring tide during the research. The second finding in the reproduction strategy uniqueness of L. scabra that mating individuals, both males, and females, released their larvae during the research period. Key Words: Littoraria scabra; uniqueness, releasing; veliger; male and female ABSTRAK Penelitian yang amat langka di alam ini menemukan kebaharuan keunikan strategi reproduksi Littoraria. scabra, di waktu kopulasi jantan berperan seks terbalik menyedot sebagian telur yang dibuahi dan dierami telur-telur yang dibuahi dalam tubuhnya sampai menetas menjadi larva-larva serta melepaskan larva-larva tersebut di bulan penuh dan baru yang mengikuti siklus pasang selama penelitian. Temuan amat langka kedua keunikan strategi reproduksi L. scabra, yang amat langka di alam dengan pasangan jantan-betina lagi kawin melepaskan larva-larva baik jantan maupun betina pada siklus bi-lunar bersamaan dengan siklus pasang selama penelitian. Kata Kunci : Littoraria scabra; keunikan,pelepasan; veliger; jantan dan betina